2019
DOI: 10.1039/c9fo00769e
|View full text |Cite
|
Sign up to set email alerts
|

Beta-hydroxy beta-methyl butyrate decreases muscle protein degradation via increased Akt/FoxO3a signaling and mitochondrial biogenesis in weanling piglets after lipopolysaccharide challenge

Abstract: The aim of this study was to investigate the effects of dietary β-hydroxy-β-methylbutyrate (HMB) on lipopolysaccharide (LPS)-induced muscle atrophy and to investigate the mechanisms involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 45 publications
2
24
0
1
Order By: Relevance
“…Thirty healthy pigs (Landrace, 21 ± 2 d, barrow, 5:86 ± 0:18 kg) were chosen and randomly assigned to three groups (n = 10): (1) nonchallenged control (CON); (2) LPS-challenged control (LPS, E. coli serotype 055:B5; Sigma Chemical, St. Louis, MO, USA); (3) LPS +0.60% HMB-Ca treatment (LPS+HMB; HMB-Ca, purity = 99:2%, Ca = 13:6%, Sipu Biochemical Co. LTD, Zhangjiagang, China). The HMB-Ca and LPS doses were used in accordance with our previous studies [12]. On days 1, 3, 5, 7, 9, 11, 13, and 15 of the trial, overnight fasted piglets of the LPS and LPS+HMB groups were intraperitoneally administered LPS, whereas piglets in the CON group were injected with the same volume of sterile saline as previously described [12].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty healthy pigs (Landrace, 21 ± 2 d, barrow, 5:86 ± 0:18 kg) were chosen and randomly assigned to three groups (n = 10): (1) nonchallenged control (CON); (2) LPS-challenged control (LPS, E. coli serotype 055:B5; Sigma Chemical, St. Louis, MO, USA); (3) LPS +0.60% HMB-Ca treatment (LPS+HMB; HMB-Ca, purity = 99:2%, Ca = 13:6%, Sipu Biochemical Co. LTD, Zhangjiagang, China). The HMB-Ca and LPS doses were used in accordance with our previous studies [12]. On days 1, 3, 5, 7, 9, 11, 13, and 15 of the trial, overnight fasted piglets of the LPS and LPS+HMB groups were intraperitoneally administered LPS, whereas piglets in the CON group were injected with the same volume of sterile saline as previously described [12].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that HMB is used as a nutritional supplement to exert positive roles in animals and humans under stressful or inflammatory conditions [11][12][13]. We recently reported that dietary supplementation with 0.60% HMB prevents muscle protein degradation and alleviates intestinal injury in LPSchallenged piglets [12,13]. Given its beneficial roles under inflammatory condition, we hypothesized that HMB may also exert positive roles in the liver of LPS-challenged piglets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical analyses were performed using SPSS Statistics software (version 20, IBM). Figures were prepared using GraphPad Prism 7.0 (GraphPad Software, La Jolla, CA, USA) [50,70,71].…”
Section: Resultsmentioning
confidence: 99%
“…Los factores relacionados con su aparición son la edad, el sexo, consumo insuficiente de proteínas, nivel de actividad física, presencia de enfermedades crónicas, disminución de hormonas sexuales y sedentarismo (14). Conforme el individuo envejece se va presentando una disminución en el número y tamaño de las fibras musculares, ocurriendo una pérdida gradual de la fuerza intrínseca de cada miofibrilla acompañada de un incremento en la infiltración de los ácidos grasos y colágeno, alterándose también la modulación neurológica de la contracción (15,16).…”
Section: Análisis Del Estado Sarcopénico En Individuos Con Enfermedadunclassified